Crossover-active regions of the wheat genome are distinguished by DMC1, the chromosome axis, H3K27me3, and signatures of adaptation - Tock, Andrew J.; Holland, Daniel M.; Jiang, Wei; Osman, Kim; Sanchez-Moran, Eugenio; Higgins, James D.; Edwards, Keith J.; Uauy, Cristobal; Franklin, F. Chris H.; Henderson, Ian R. (Genome Research, 2021)
The hexaploid bread wheat genome comprises over 16 gigabases of sequence across 21 chromosomes. Meiotic crossovers are highly polarized along the chromosomes, with elevation in the gene-dense distal regions and suppression in the Gypsy retrotransposon-dense centromere-proximal regions. We profiled the genomic landscapes of the meiotic recombinase DMC1 and the chromosome axis protein ASY1 in wheat and investigated their relationships with crossovers, chromatin state, and genetic diversity. DMC1 and ASY1 chromatin immunoprecipitation followed by sequencing (ChIP-seq) revealed strong co-enrichment in the distal, crossover-active regions of the wheat chromosomes. Distal ChIP-seq enrichment is consistent with spatiotemporally biased cytological immunolocalization of DMC1 and ASY1 close to the telomeres during meiotic prophase I. DMC1 and ASY1 ChIP-seq peaks show significant overlap with genes and transposable elements in the Mariner and Mutator superfamilies. However, DMC1 and ASY1 ChIP-seq peaks were detected along the length of each chromosome, including in low-crossover regions. At the fine scale, crossover elevation at DMC1 and ASY1 peaks and genes correlates with enrichment of the Polycomb histone modification H3K27me3. This indicates a role for facultative heterochromatin, coincident with high DMC1 and ASY1, in promoting crossovers in wheat and is reflected in distalized H3K27me3 enrichment observed via ChIP-seq and immunocytology. Genes with elevated crossover rates and high DMC1 and ASY1 ChIP-seq signals are overrepresented for defense-response and immunity annotations, have higher sequence polymorphism, and exhibit signatures of selection. Our findings are consistent with meiotic recombination promoting genetic diversity, shaping host–pathogen co-evolution, and accelerating adaptation by increasing the efficiency of selection.